Appointments of rural preceptors in postwar Paraguay (1880-1886) - García Riart, Jorge (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: To identify the appointments of rural preceptors in an inland village of Paraguay between 1880 and 1886, twenty years after the War of the Triple Alliance. Originality/Contribution: Delve into the topic of the restoration of public education during this period, as well as the political reorganization of Paraguay. Method: Qualitative, descriptive and inductive approaches are adopted to study the appointments of preceptors and preceptresses in Villa Florida, a rural village of Paraguay. These methods allow us also to formulate general conclusions about political reorganization and public education. Strategies/Data collection: Handwritten sources such as the decrees of appointments in the Official Public Records and in the Education-Ministry of Justice Section at the National Archives of Asuncion, and some secondary sources are reviewed in order to quantify the creation of rural schools, from 1st to 3rd grade, and then relate the appointments of preceptors coinciding with that of political leaders and justices of the peace. Conclusion: The list of appointments of preceptors concatenated with that of political leaders and justices of the peace demonstrates -through personal and family accommodations- the formation of a new institutional bureaucracy that supports the preeminence of political reorganization over the reorganization of public education that took place in the second postwar decade in Paraguay.